PENGEMBANGAN SOFT SKILLS DAN RELIABILITY UNTUK MENINGKATKAN KUALITAS PELAYANAN DAN KEPUASAN NASABAH - Purwanto, Agus Budi (BBM (Buletin Bisnis & Manajemen), 2015)
AbstractThis research is motivated declining number of Bank Perkreditan Rakyat (BPR). Decreasing the number of BPR indicate unhealthy condition. In general, this study aims to determine the model of the development of soft skills and reliability of  banking employees in order to improve service quality and increase customer satisfaction. Specifically, this study aims to improve the quality of governance, healthy operational management and professional in the banking world. The model used in this study is comprised of four variables where the variables in the first stage of soft skills and reliability of the independent variable while the quality of service becomes the dependent variable. Then in the second stage of skill and reliability as an independent variable, the quality of service as an intervening variable, whereas the variable customer satisfaction as the dependent variable. Research data collection techniques by means of a questionnaire on BPR customers spread in Semarang systematically arranged with multiple choice answers are easy to understand. Distribution of the questionnaire by means of a direct encounter conducted in the period April to August 2014, with a sample of some 120 people. Instrument (questionnaire) will go through the stages of validity and reliability. Research data will be analyzed using path analysis (path analysis). Test the strength of the model using SEM (Structural Equation Modeling). The research proves that there is a direct positive influence between soft skills and reliability to customer satisfaction. The results also prove that the quality of service is a positive intervening between soft skills and reliability to customer satisfaction.                                                       Keywords: soft skills, reliability, quality of service, customer satisfaction